THE EFFECT OF GOOD CORPORATE GOVERNANCE TOWARD FIRM PERFORMANCE ON BANKING SECTOR LISTED IN INDONESIA STOCK EXCHANGE (IDX) FROM 2015-2019 - admin, KELLY CHANDRA B1024171014 (Jurnal Manajemen Update, 2021)
This research discuss about the effect of Good Corporate Governance toward firm performance of banking companies. This research use 32 banking companies listed in IDX from 2015-2019. The independent variables used are activities (meetings) of Board of Commissioners (X1), size of Board of Directors (X2), size of Board of Independent Commissioners (X3), and size of Audit Committee (X4), while the dependent variable used are Tobin’Q (Y1) and Price-to-Book Value (Y2). The data collected will be processed using panel data regression on the basis of Fixed Effect Model. The final results shown by this research are various depends on the dependent variable used. With Tobin’Q as the dependent variable, X2 and X3 have positive insignificant effect toward firm performance, meanwhile X1 and X4 have negative insignificant effect toward firm performance. With PBV as the dependent variable, only X3 have positive significant effect toward firm performance, meanwhile X1, X2, and X4 have negative insignificant effect toward firm performance.